THE EFFECT OF LITTLE AND MEDIUM E- BUSINESS ENTERPRISES ON THE MALAYSIAN ECONOMY - Yajid, Mohd Shukri Ab; Ghazali, Abdul Jalil; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this assessment was to fabricate the present perception and commonality with the factors that sway assignment of e-business. The model that was created recommended that reception of e-business could be displayed with six recognizable factors; e-business nuts and bolts (EB), pioneering profile (EP), e- business methodologies (ES), e-business benefits (EBF), e-business obstructions (EBS) and e-business future course (EFD). The model was tried with an example of 200 Malaysian respondents. The surveys were circulated among SME business visionaries inside various fields. Moreover, there was a position relationship for introduction level towards the appropriation of e- business. The information examination utilized in the exploration were; distinct insight, ordinariness test, homogeneity test, relationship, ANOVA, think about mean, multi co linearity and research estimation strategy including Chi square, Numerous Direct relapses and factor investigation. The outcomes showed every one of the six recognizable factors were huge in upgrading understanding and exhibit the helpfulness respects spurring SME business visionaries to receive e-business.